The Islamic Religious Education Service Marketing Management at KUA Talang Ubi - Asmuni Asmuni; Zainal Berlian; Ahmad Zainuri (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2024)
Islamic religious education is one of the important sectors in the development of a community with character and noble values. The KUA Talang Ubi, as a religious institution, plays an active role in providing Islamic education services, including pre-marriage counseling and family education for a harmonious family life (sakinah). This study aims to analyze the implementation of service marketing management elements at KUA Talang Ubi, focusing on product, place, process, promotion, and physical evidence. Using a descriptive qualitative approach, this research identifies the successes and challenges in managing Islamic education services. The findings indicate that although the marketing management implementation is running well, there are still challenges such as the lack of adoption of the SIMKAH technology by the community and inconsistent implementation of standard operating procedures (SOP). This article offers recommendations in the form of intensive training for the community, improved communication quality, and staff training.